Public perceptions of 'negging': lowering women’s self-esteem to increase the male attractiveness and achieve sexual conquest - Green, Kathleen; Kukan, Zoe; Tully, Ruth (Emerald, 2017)
Purpose: ‘Negging’ can be described as the purposeful lowering of a woman’s self-esteem to increase perceived attractiveness of the man in order to achieve sexual conquest. Negging has evolved over time. Whilst ‘Original’ negging was intended to be a harmless tool for attracting women, more recently dating companies have been teaching men ‘Evolved’ negging in a potentially damaging way, which could escalate into an abusive intimate relationship. Design: An online survey involving vignettes depicting negging between strangers with three conditions; ‘Original’, ‘Evolved’ and ‘Control’ was completed by 308 participants. Participants were asked how harmful, acceptable, and how likely to escalate each scenario was. A fourth vignette described ‘Evolved’ negging between partners. Results: Mixed methods ANOVA indicated that participants perceived all negging as being significantly more harmful than control ‘pick-up’ lines. ‘Evolved’ negging was considered to be more likely to escalate in seriousness than ‘Original’ negging. Conclusions: Despite the public viewing negging as harmful and with the potential to escalate in seriousness, women are still being targeted in this manner and the industry ‘teaching’ negging is growing despite controversy. This study aims to increase general awareness of negging in order to minimise harm caused to women who are ‘picked-up’ through this technique. To this end, directions for future research are highlighted. Originality: This paper is one of the first empirical studies in the area of negging. The perceived, and potential, harm caused can be studied in light of these novel findings with the aim of protecting women from harm.